MODEL KOMUNIKASI MUDIR MA'HAD SEBAGAI LEADER DI TARBIYATU MUALLIMIEN AL-ISLAMIYAH PUTRI PONDOK PESANTREN AL-AMIEN PRENDUAN - Dini Nur Jannah (Al-Amien Prenduan University, Sumenep, 2020)
Abstract Leader and communication have a tight relation, that a communicative of leader relation to staff communication, like to arrange and to join a program which never before. The problem from this research is communication model of mudir ma’had as leader of Tarbiyatul Muallimien Al-Islamiyah for female Al-Amien Islamic boarding school Prenduan Sumenep Madura year 2017-2018 which the researcher gets several problems in this research are: 1. How communication process is used by Mudir Ma’had as leader in Tarbiyatul Muallimien Al-Islamiyah for female Al-Amien Islamic Boarding School Prenduan Sumenep Madura year 2017-2018? 2. What communication model is used by Mudir Ma’had as leader in Tarbiyatul Muallimien Al-Islamiyah for female Al-Amien Islamic Boarding School Prenduan Sumenep Madura year 2017-2018? The researcher used the qualitative descriptive. The method used are interview, observation, and documentation. From this method, researcher analyze for getting data and information. This research subjects are head master of junior high school (Mr. Zainal Abidin, S. Sos. I), Secretary of Idaroh Ma’had and Idaroh Ma’had staffs. For validating data, researcher used sources triangulation is head master of junior high school and Secretary of Idaroh Ma’had. After getting data, researcher found communication process is used by Mudir Ma’had as leader in Tarbiyatul Muallimien Al-Islamiyah for female Al-Amien Islamic Boarding School Prenduan Sumenep Madura year 2017-2018 is primary process, and communication model is used by Mudir Ma’had as leader in Tarbiyatul Muallimien Al-Islamiyah for female Al-Amien Islamic Boarding School Prenduan Sumenep Madura year 2017-2018 is transactional model. Key Words : Communication model, Leader